Acesso permitido: modelo de implementação da audiodescrição fílmica na Cinemateca Virtual Guarnicê para pessoas com deficiência visual - SILVA, Saulo Simões da (2024)
Equitable and equal access to culture, education, and all spheres of life is a fundamental human right and essential in the formation of the individual, regardless of their abilities or limitations. In this exploratory, qualitative, and applied study, we propose a model for implementing audio description (AD) of films in the “Cinematic Virtual Guarnicê”, guided by the approaches of Inclusive Design (ID) and Human- Centered Design (HCD), to enable the insertion of this assistive resource, making this collection more accessible and inclusive for people with visual disabilities: blind or low vision. The stages of the Design Science (DS) method structured the methodological trajectory of this research, including: (1) Problem Understanding, (2) Alternative Generation, (3) Development, and (4) Evaluation. The information gathering began with documentary research in primary sources, concurrently with the Narrative Literature Review (NLR), in order to demarcate a robust and coherent theoretical body addressing people with disabilities; disability models; people with visual disabilities; Inclusive Design and Human-Centered Design; assistive technologies; audio description and audio describers. Finally, cinematheque, with emphasis on the “Cinematic Guarnicê” and the implementation of its online and accessible version. The semi-structured interview with specialists concluded the data collection stage. The content analysis procedures in the informants' responses supported the Ideation of the artifact. For the ideation phase, a conceptual map was elaborated in accordance with the nature of its application and based on the information resulting from the problematization stage. Based on the conceptual map, a set of recommendations for the model of implementation of film audio description in the “Cinematic Virtual Guarnicê” was summarized. The model was evaluated using a questionnaire tool with closed questions, the obtained data were treated in light of the content analysis method, using the thematic analysis technique. The results of this procedure were directed towards the refinement of the recommendations, so that the model can effectively contribute to the inclusion, equity, and autonomy of people with visual disabilities, in the “Cinematic Virtual Guarnicê” of the Federal University of Maranhão (UFMA) and, with adaptations, in other contexts.